Wireframe Creation on SIOBEL Application User Interface Design using User Centered Design - Wibawani, Sri; Terza Damaliana, Aviolla; Setiawan, Ariyono; Mas Diyasa, I Gede Susrama; Dwi Kusuma, Irma (Information Technology International Journal, 2023)
The development of an interactive SIOBEL (Sistem Informasi Bela Neagara) application requires the application of User Centered Design in the UI/UX design phase. In this context, User Centered Design becomes an important cornerstone in ensuring an optimal user experience and meeting the needs of users when using the SIOBEL application as a platform to integrate state defense values with oubound. By applying UCD, the UI/UX wireframe design of the SIOBEL application can create a better and satisfying user experience. Users will feel engaged and comfortable when using the application.